Organizational Commitment as the Key to Improving Lecturer Performance: Empirical Study on Private Universities - Syahsudarmi, Siti; Norawati, Suarni; Yusuf, M; Yusriadi, Yusriadi; Yantama, Akmal Andri (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the influence of organizational support and organizational culture on lecturer performance, with organizational commitment as a mediating variable. The research design used a quantitative approach with an explanatory survey method. The study population included all certified permanent lecturers in economics study programs at private universities in Riau Province, with a sample of 150 lecturers selected through purposive sampling. The research instrument was a five-point Likert scale questionnaire that was tested for validity and reliability before use. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS. The results showed that organizational culture had a positive and significant effect on organizational commitment, and organizational commitment has a substantial impact on lecturer performance. In addition, organizational culture had an indirect effect on performance through organizational commitment. Conversely, organizational support was not proven to have a significant impact on either lecturer commitment or performance. This study found that cultural factors have a more dominant role than administrative support in driving performance. Practically, the implications of this study suggest that higher education leaders should prioritize strengthening an academic culture that fosters lecturer loyalty and engagement, thereby enabling continuous improvement in the performance of the tridharma.